Formação Inicial e Práticas Pedagógicas de Pibidianos, subprojeto Ciências da UNIFESP - Valiengo, Ana Lucia Carvalho [UNIFESP] (2020)
The present work aims to investigate the pedagogical practice of scholarship holders of the Institutional Program for Teaching Initiation Scholarships - PIBID, Science subproject, of the Science-Degree course at UNIFESP, Campus Diadema and to analyze the contributions of the Program in the initial training process of students of graduation. The subproject Sciences was developed at Escola Estadual Padre Anchieta, a partner school of the Program, located in Diadema-SP. PIBID is a program aimed at the initial training of undergraduate students, with the purpose of providing them with educational and training experiences, through the direct contact of these future teachers with the classroom. This is a qualitative approach research, a case study method, as it adapts to the best understanding of the classroom, having as main instruments of construction and data analysis, document analysis, semi-structured interviews and observations. In the first stage of the investigation, the fellows / volunteers and supervisor of the Science subproject, answered questionnaires to survey the profile. Subsequently, semi-structured interviews were conducted with the eleven graduates and program supervisor who worked on the subproject and analysis of the lesson plans. Based on the analysis of the lesson plans and planning, implementation, reflection and evaluation of the proposed activities, it allows us to conclude that the actions developed in the Science / UNIFESP subproject, made it possible to develop autonomy to deal with various situations experienced and promoted an academic-professional formation, articulating theory and practice, evidenced in practices articulated with the reality of the school and committed to the challenges inherent in the classroom's daily life. The responses of the undergraduate and supervisors signal the need for the continuity and expansion of the program, considering the importance of professional development, initial and continuing education, valuing the teaching profession and improving the quality of teaching, as well as the need for new actions and new ones. research in the area. Consistent with the information presented, PIBID contributed to the initial training of students in the Science-Degree course at UNIFESP, in the integration of different teaching knowledge, articulating theory and practice and in improving the quality of Science teaching, through different pedagogical strategies developed in the school space, the privileged locus to action / reflect and reflect / actin.